MODEL SOAL UJIAN NASIONAL MATA PELAJARAN MATEMATIKA SMP DITINJAU DARI KRITERIA NATIONAL ASSESSMENT OF EDUCATIONAL PROGRESS - bettri yustinaningrum (EduMa: Mathematics education learning and teaching, 2015)
The research aims to: obtaining (1) a description of the types of materials , mathematical ability, and the level of complexity, (2) a description of the absorption of the material, (3) a model of matter UN in terms of NAEP as an alternative evaluation of learning mathematics. This study uses a model of Plomp development consisting of preliminary investigation, design, the realization phase, test, evaluation, and revision, and implementation phases. Type of device being developed is the UN test criteria were reviewed from NAEP and validation sheet. The device is validated experts and colleagues then tested on the subject of new students of class X-2 SMAN 2 Mranggen. The test results were analyzed with biserial correlation, product moment, Hoyt, level of difficulty and discrimination power. The first trial invalid on multiple-choice number 4, 5, 14,15, 16, and 17. Reliability in one package at a high 0.931. The second trial on multiple-choice questions that all valid. At number 7 short answer is invalid, and valid for all extended construction. Reliability on the second package of 0.904 is high. To be able to apply this test the model is necessary to develop and test further.Keywords : NAEP, Procedural Knowledge, Understanding Concepts, Problem Solving, Absorption Student